Uterine Torsion with a 1080° Rotation in a Queen with Closed-cervix Pyometra - de Oliveira, Sidnei Nunes; Hayashi, Rafaella Miki; Dalanezi, Felipe Morales; de Araújo, Endrigo Andonis Braga; Zahn, Fabíola Soares; Silva, Luís Fernando Mercês Chaves; Rodrigues, Jéssica Corrêa; Prestes, Nereu Carlos (Acta Scientiae Veterinariae, 2016)
Background: Uterine torsion is a rotation of one or both uterine horns around its longitudinal axis, associated to vascular compromise that may lead to necrosis and both metabolic and hematological disorders, rarely reported in cats. The etiology has not been established and it has most frequently been associated to pregnancy, although its occurrence in non-pregnant animals in association with uterine diseases (e.g. pyometra, mucometra and hematometra) has been reported. The aim of this work is to report a case of 1080° uterine horn torsion in a cat with closed-cervix pyometra. Case: A five-year-old, weighing 4.2 kg, female queen was referred to the Ambulatório de Pequenos Animais do Departamento de Reprodução Animal e Radiologia Veterinária in the Veterinary Hospital of Universidade Estadual Paulista “Júlio de Mesquita Filho”, Botucatu, SP with a three-day history of an evident abdominal distension, anorexia, polydipsia and lethargy. The owner reported that the queen had delivered a litter of kittens three years ago and, since then, medroxyprogesterone acetate has been administrated in order to inhibit the oestrus cycles. Physical examination revealed pale mucous membranes, dehydration, cachexy, abdominal distension with no vaginal discharge and a large uterus with irregularities, detected by abdominal palpation. Hematological examination revealed anemia, thrombocytopenia, leukocytosis, hyperglycemia and metabolic acidosis. Ultrasonographic examination revealed hypoechogenic fluid uterine content, suggesting closed-cervix pyometra associated to clinical signs of sepsis. An exploratory laparotomy was performed; the uterus was externalized and revealed a 1080° torsion of the congested and distended left uterine horn with vascular compromise and some foci of necrosis; the right uterine horn had a normal appearance but was also distended. Ovariohysterectomy was performed and the diagnosis of pyometra was confirmed by the evaluation of uterine content. Pre- and postoperative medical supportive therapy were performed and the queen recovered successfully. Discussion: The administration of medroxyprogesterone acetate predisposed the queen to cystic endometrial hyperplasia/ pyometra complex and the absence of vaginal discharge characterized a closed-cervix pyometra, the more severe form of the disease, thus leading to severe sepsis. In this case, abdominal palpation should be careful because of the uterine wall fragility, which could lead to uterine rupture and peritonitis; therefore ultrasonography is the technique of choice to confirm this pathology, although the uterine torsion cannot be diagnosed with this exam. This disease can only be confirmed by exploratory laparotomy. The etiology has not been established, but this case can be associated with stretching of both the ovarian pedicle and broad ligament by a previous pregnancy and by the uterine distension provided by pyometra. The degree of uterine torsion identified in this case is an uncommon finding. It may potentially cause severe complications in the queen, including peritonitis, septicemia, endotoxemia and disseminated intravascular coagulation and may lead to death if the cat does not have a prompt surgical intervention with an effective pre- and postoperative medical supportive therapy. Therefore the establishment of a prognosis of uterine torsion cases in the queen is correlated with these aspects. Keywords: feline, uterine torsion, contraceptive, endometrial cystic hyperplasia.